Validity Analysis of Heyzine Assisted Learning Project Based Electronic Modules in Facilitating Students' Creative Thinking Skills on Climate Change Material - M Ilham; Dea Stivani Suherman; Ratnawulan Ratnawulan; Fadhila Ulfa Jhora (Journal of Innovative Physics Teaching, 2026)
Creative thinking is a crucial skill in 21st-century learning, yet field conditions indicate that students' creative thinking abilities remain relatively low. This is due to the use of teaching materials that fail to facilitate the development of student creativity and the suboptimal implementation of project-based learning models in the classroom. To address this issue, this research focuses on the development of a project-based learning electronic modules designed to support and enhance students' creative thinking skills. This research employed a Research and Development (R&D) method with a 4D development model, which includes the definition, design, and development stages. In the definition stage, observations were conducted in several schools. The next stage, the design stage, involved developing a framework for the project-based learning electronic modules. In the development stage, the designed product was tested through validity and practicality tests. Data collection instruments in this study included teacher interviews, student questionnaires, and validity and practicality test sheets. The data obtained were then analyzed using validity analysis techniques with Kappa Moment (k) and product practicality analysis. The results showed that the developed electronic modules had a validity value of 0.86, which is categorized as very valid. It can be concluded that the developed project-based learning electronic modules are valid for improving students' creative thinking skills.